2013
DOI: 10.1080/00380768.2013.864957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exponential fertilization on growth and nutritional status in Buddhist pine (Podocarpus macrophyllus[Thunb.] D. Don) seedlings cultured in natural and prolonged photoperiods

Abstract: Slow growth rate limits the development of seedlings from the Podocarpaceae family. The extended photoperiod (EP) is well known to promote tree seedling growth, but it may also cause the possibility of nutrient dilution without a proper nutrient supply regime. Exponential fertilization (EF) has been proven to counter nutrient dilution within tree seedlings efficiently. However, no study has determined the response of Podocarpus seedlings to the interaction of EF and photoperiod. We fed 13-month old Buddhist pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 19 publications
6
53
3
Order By: Relevance
“…needles vs. broad attributing to specific leaf area (Nagel et al, 1998). In contrast to our results of the null response of Buddhist pine seedlings to photoperiod, an earlier study suggested a stimulated response to height of juvenile Buddhist pine seedlings in response to extended photoperiod (Wei et al, 2013). The most reasonable explanation of these varied responses can be concluded due to the difference of lightsensitivity driven by plant developmental stages.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…needles vs. broad attributing to specific leaf area (Nagel et al, 1998). In contrast to our results of the null response of Buddhist pine seedlings to photoperiod, an earlier study suggested a stimulated response to height of juvenile Buddhist pine seedlings in response to extended photoperiod (Wei et al, 2013). The most reasonable explanation of these varied responses can be concluded due to the difference of lightsensitivity driven by plant developmental stages.…”
Section: Discussioncontrasting
confidence: 56%
“…Because leachates were collected by traits immediately after irrigation until the volume of 100 mL, therefore declined P loss may result from increased P uptake by seedlings of the two species under extended photoperiod. Wei et al (2013) revealed that under extended photoperiod P uptake was fully promoted by needles, stem, and root of Buddhist pine seedlings. Accordingly, photoperiod was also found to affect P requirement for the maximum growth rate (Shatwell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations